2020
DOI: 10.1161/hypertensionaha.120.14974
|View full text |Cite
|
Sign up to set email alerts
|

Affinity-Enhanced Multimeric VEGF (Vascular Endothelial Growth Factor) and PlGF (Placental Growth Factor) Variants for Specific Adsorption of sFlt-1 to Restore Angiogenic Balance in Preeclampsia

Abstract: Preeclampsia is a potentially life-threatening multisystem disease affecting 4% to 8% of pregnant women after the 20th week of gestation. An excess of placental expressed antiangiogenic soluble VEGF (vascular endothelial growth factor)-receptor 1 (soluble FMS-like tyrosine kinase 1) scavenges VEGF and PlGF (placental growth factor), causing generalized endothelial dysfunction. Interventions to restore the angiogenic balance in preeclamptic pregnancies are intensively studied and improve ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…More recent experimental therapeutic approaches are investigating the possibility of using apheresis to reduce sFlt-1 levels. A significant reduction in sFlt-1 serum concentrations has been achieved in small pilot studies which showed an alleviation of maternal symptoms including a reduction of maternal hypertension and proteinuria and increased fetal growth based on fetal percentile curves 108 , 109 , 110 . In addition, studies have shown that this delayed immediate delivery of the infant by 2 – 21 days.…”
Section: Specific Causes Of Pr-akimentioning
confidence: 99%
See 1 more Smart Citation
“…More recent experimental therapeutic approaches are investigating the possibility of using apheresis to reduce sFlt-1 levels. A significant reduction in sFlt-1 serum concentrations has been achieved in small pilot studies which showed an alleviation of maternal symptoms including a reduction of maternal hypertension and proteinuria and increased fetal growth based on fetal percentile curves 108 , 109 , 110 . In addition, studies have shown that this delayed immediate delivery of the infant by 2 – 21 days.…”
Section: Specific Causes Of Pr-akimentioning
confidence: 99%
“…Neuere experimentelle Therapieansätze untersuchen die Möglichkeit der Reduktion von sFlt-1 mittels Apherese. In kleineren Pilotstudien ließ sich zum einen eine signifikante sFlt-1-Konzentrations-Senkung im Serum, zum anderen eine Erleichterung der mütterlichen Symptome wie Einstellung des Blutdrucks und Abnahme der Proteinurie als auch ein gesteigertes Wachstum auf der Perzentilenkurve der Feten nachweisen 108 , 109 , 110 . Weiterhin ließ sich eine notwendige sofortige Entbindung um 2 – 21 Tage verzögern.…”
Section: Spezifische Ursachen Des Pr-akiunclassified
“…sFlt-1 binds to VEGF and PGF to inhibit their proangiogenic process ( 130 ). sFlt-1/VEGF imbalance leads to endothelial dysfunction and angiogenic disorder in patients with PE ( 131 , 132 ). The sFlt-1/VEGF ratio has emerged as a key biochemical indicator for predicting the risk of PE ( 113 ).…”
Section: Mesenchymal Stem Cells In Preeclampsia Therapymentioning
confidence: 99%
“…This hypothesis of the pathophysiology of preeclampsia has led to the development of strategies to restore the angiogenic balance. The removal of sFlt-1 from the circulation by apheresis has shown promising results as a potential treatment of preeclampsia, since increases the levels of free VEGF and PlGF in serum samples of preeclamptic patients ( Matin et al, 2020 ).…”
Section: Is the Endothelial Dysfunction At The Bbb In Preeclampsia A ...mentioning
confidence: 99%